The Effect Of Job Stress And Organizational Climate On Turnover Intention: Mediating Role Of Job Satisfaction - Wibowo, Bagus Handaru Mukti; Margono, Margono; Noermijati, Noermijati (International Journal of Business, Law, and Education, 2023)
This research is intended to investigate The Effect of Job Stress and Organizational Climate on Turnover Intention through job satisfaction. This research used a sample of Bank BPD Jatim Kota Malang employees using a saturated sampling technique. A sample of 135 respondents was obtained which was analysed using structural equation modelling partial least squares with Smartpls software. The research results show that job stress directly affect turnover intention, meanwhile, the organizational climate does not show a direct effect on turnover intention. Then, job satisfaction has a significant effect on turnover intention However, with the mediating variable job satisfaction, these two variables become significant